Psychological and Societal Impacts of Unknown Descent and The Islamic Objective of Nasab. A Preliminary Study of Chosen Biomedical Technologies - Bouzenita, Anke Iman; Hussain, Feryad A (IIUM Medical Journal Malaysia, 2021)
This paper is a preliminary study on the expected implications of some chosen biomedical developments on the loss of descent (nasab), its psychological effects on children and parents, and sociological effects generally. In the first part, this paper elaborates the meaning and importance of nasab (descent) in Islamic law, under consideration of the Higher Objectives of Shari’a, and explanation of some related legal rules. The second part investigates psychological impacts of unknown descent and reviews existing research in the field. The third and final part, presents five chosen scenarios i) human cloning through somatic cell nuclear transfer (SCNT); ii) surrogate motherhood; iii) IVF with sperm or egg donors; iv) anonymous milk banks; and v) mitochondria (mt) transplantation; in the light of the Islamic objective of nasab, its existence or non-existence, and possible consequences.